Psycho-Educational Program and Guided Imagery on Reducing Anxiety for Groups of Pregnant-Woman in Candi Urban Village Under Surveillance of Kagok Public Health Center in Semarang City - Florencia Astari Wijaya; Christin Wibowo; Erna Agustina Yudiati; Esthi Rahayu (JURNAL KEBIDANAN, 2023)
Pregnancy is a transition phase on a woman’s life when they enter marriage and oftentimes anxiety during pregnancy can induce in this phase especially third trimester. Psychoeducation is a treatment given to an individual to strengthen their coping mechanism which undergoes mental health problems such as anxiety. In addition to providing knowledge through psychoeducation, groups of pregnant woman can also be given treatment through relaxation technique as Guided Imagery. The research is conducted at Kagok Public Health Center Semarang with 5 respondents sample size were all third trimester pregnant women. Quasi experimental design pre-post test approach is used in this experiment. Several assessment that has been conducted in this experiments were observation, interview, and Focus Group Discussion (FGD). The measurement used anxiety scale which compiled by the researcher by adopting Perinatal Anxiety Screening Scale (PASS). Statistical test analysis using Wilcoxon Signed Ranks. The result of research showed that interventions can reduce a level of anxiety if appropriate with the procedure which has been set. There is a significant differences of anxiety levels on groups of pregnant woman trimester III. The results of statistical analysis using Wilcoxon Signed Rank Test showed that p value was 0,000 (p. value 0,05) illustrating that psychoeducation program and guided imagery were effective on the level of anxiety experience by the groups of pregnancy women in the third trimester in Candi Urban urban village under surveillance of Kagok Public Health Center in Semarang City. This study can be a knowledge for citizen especially groups of pregnant-woman that psychoeducation and guided imagery technique are alternative intervention for reducing anxiety toward the childbirth for expectant mother